Learner-Centered Debriefing for Health Care Simulation Education: Lessons for Faculty Development. Issue 1 (February 2016) - Cheng, Adam; Morse, Kate J.; Rudolph, Jenny; Arab, Abeer A.; Runnacles, Jane; Eppich, Walter
Abstract : Summary Statement: Better debriefing practices may enhance the impact of simulation-based education. Emerging literature suggests that learner-centered debriefing may be effective in helping instructors identify and address learner needs while building learner's engagement and sense of responsibility for learning. This contrasts with instructor-centered approaches to debriefing, where instructors maintain unilateral control over both the process and content of the debriefing, thus limiting input and direction from learners. Although different approaches to debriefing for simulation-based education exist, the simulation literature is largely mute on the topic of learner-centered debriefing. In this article we will (1) compare and contrast learner- versus instructor-centered approaches to teaching; (2) provide a rationale for applying more learner-centered approaches to debriefing; (3) introduce a conceptual framework that highlights the key dimensions of learner- versus instructor-centered debriefing; (4) describe key variables to consider when managing the balance between learner- and instructor-centered debriefing; and (5) describe practical learner-centered strategies for various phases of debriefing.